Deacidification of crude palm oil using PVA-crosslinked PVDF membrane. (December 2015) - Azmi, R.A.; Goh, P.S.; Ismail, A.F.; Lau, W.J.; Ng, B.C.; Othman, N.H.; Noor, A.M.; Yusoff, M.S.A.
Highlights: CPO deacidification using pressure-driven membrane system without the addition of any chemicals. PVDF hollow fiber membrane were crosslinked with various concentration of PVA. Significant changes on the contact angle and surface roughness of the crosslinked membrane. PVDF crosslinked with 100 ppm PVA exhibit the highest rejection of FFA. Abstract: Over recent years, there has been an explosive growth of interest in the development of alternative approaches for crude palm oil (CPO) refining. During a typical refinery process, free fatty acid (FFA) is one of the key objectionable impurities that need to be reduced if not completely removed from CPO in order to minimize their detrimental effects on the oil quality. Polyvinylidene fluoride (PVDF) membrane shows great potential in removing FFA from CPO owing to its hydrophobic properties, high mechanical strength and good thermal stability. However, low concentration of FFA in CPO, which is normally ranging from 3% to 5%, has hindered the capability of the membranes to separate the trace amount of FFA from the bulk. Thus, modification of PVDF membrane is essential to enhance the interaction between the membrane surface and FFA molecules, facilitating efficient FFA removal. In order to achieve this purpose in the present study, the outer surface of PVDF hollow fiber membranes was crosslinked with polyvinyl alcohol (PVA). Glutaraldehyde (GA) was used as a crosslinking agent to avoid the PVA dissolution. Despite the negligible morphological change observed in the resultant membranes upon PVA crosslinking, the contact angle has been significantly reduced in proportional to the concentration of PVA used for the crosslinking, suggesting the decrease in membrane hydrophobicity. Additionally, the average roughness of the crosslinked PVDF membranes increased with the increasing PVA concentration. The results obtained suggested that the PVDF hollow fiber crosslinked with 100 ppm PVA exhibited the highest FFA rejection of 5.93% after 3 h of operation. In addition, the membrane also showed good result in reducing the content of phosphorus in the permeate and partial reduction of its color intensity. This study served as the first attempt of CPO deacidification through UF membrane system without the addition of any chemical during the filtration process.